Efforts to Increase the Accountability of the National Zakat Agency According to the Perspective of Intellectuals in Pekanbaru City - Wali Saputra (Al-Buhuts, 2022)
This study aims to determine the assessment and efforts to improve the accountability of the National Zakat Agency from the perspective of the intellectual circles of Pekanbaru City. This study uses primary data obtained through observation and interviews with intellectuals who are congregations who have been or are currently involved as amil zakat in plenary mosques in Pekanbaru City as a Zakat Collecting Unit in collaboration with the National Zakat Agency of Pekanbaru City. The data analysis method in this study used a qualitative descriptive analysis. The results show that the accountability of the National Zakat Agency of Pekanbaru City is still not optimal in terms of compliance with sharia decisions in contractual transactions with muzakki, aspects of trust in the use of zakat funds, aspects of disclosure of zakat funds, and aspects of organizational governance. Efforts that must be made to increase accountability are first, increasing transparency in the management, receipt and distribution of zakat funds to the public; second, rejuvenating the management of institutions that have caused minimal creativity and innovation in the management of zakat; third, it is not easy to be dragged into the realm of practical politics in the region; fourth, increasing the professionalism of supervisors and zakat operators through training and increasing performance compensation; fifth, increasing monitoring of the publication of monthly, quarterly, semester, and annual reports on the accountability of community zakat funds; sixth, giving awards for work performance and imposing strict sanctions against violations imposed on all management; seventh, increasing socialization and submitting reports to muzakki through mosques and small mosques about where zakat has been distributed; eighth, strive for the financial statements to be audited by a reputable public accounting firm on a regular basis every year.